The complete chloroplast genome of an Endangered species Cymbidium Nanulum (Orchidaceae) - Zhang, Yong-Qiang (Mitochondrial DNA B Resour, 2019)
Cymbidium nanulum Y.S.Wu & S.C.Chen is an IUCN Red listed Endangered species and distributes in South-Central China and Hainan. Here, we report the complete chloroplast (cp) genome sequence and the cp genome features of C. nanulum. The complete chloroplast (cp) genome sequence of C. nanulum was 149,776 bp in length. It presented a typical quadripartite structure including one large single-copy region (LSC, 85,392 bp), one small single-copy region (SSC, 14,210 bp), and two inverted repeat regions (IRs, 25,087 bp). The cp genome encoded 133 genes, of which 104 were unique genes (77 protein-coding genes, 23 tRNAs, and 4 rRNAs). The maximum-likelihood phylogenetic analysis showed that C. nanulum was closely related to other species of genus Cymbidium.